Assessing the Risk of Health, Social, and Fiscal Events in Schizophrenia According to Remission or Relapse Status Using Real World Data from a SCZ Survey in the US. (April 2022) - Kadakia, Aditi; Martins, Rui; Fan, Angela; Dembek, Carole; Connolly, Mark; Shepherd, Jason; Williams, Rhys
Abstract: Background: Schizophrenia-related, health, social, and fiscal consequences are substantial, affecting patients, caregivers, and society. The incidence of health, social, and fiscal outcomes are frequently reported for the overall schizophrenia population, not stratified by remission or relapse status. Objectives: This study aimed to assess healthcare resource use, employment status, and housing circumstances for patients with schizophrenia in remission or relapse, compared to the overall schizophrenia population. Methods: The Adelphi Schizophrenia Disease Specific Programme was a point-in-time survey conducted across the USA between July and October 2019. Remission was defined using Clinical Global Impression-Severity (CGI-S) score of 1-3 (stable), with relapse defined as a CGI-S score of 4-7 (unstable). Outcome-specific rate ratios were calculated by dividing the cumulative incidence for those in remission or relapse by the cumulative incidence of the overall schizophrenia population. Ratios greater than 1 indicate a higher probability of the event. Results: Psychiatrists (n = 124) provided data for 409 patients in remission and 609 patients in relapse. Patients with schizophrenia in remission were more likely to be employed (1.66, 95% confidence interval [1.46-1.90]) and to live with a partner or family (1.08 [1.01-1.17]) compared to the overall schizophrenia population, whereas patients in relapse were more likely to experience hospitalizations in the previous 12 months (1.34 [1.19-1.15]), disability-related unemployment (1.38 [1.25-1.51]), sick leave absences (1.23 [0.66-2.31]), need to support housing (1.39 [1.08-1.79]), and homelessness (1.47 [0.95-2.27]). Conclusions: Schizophrenia patients in relapse were more likely to experience hospitalizations, unemployment, and have unfavorable housing circumstances compared to the overall schizophrenia population. Identifying patients at risk of relapse may aid physicians in targeting interventional support, thereby reducing the burden of schizophrenia. Funding: Sunovion Pharmaceuticals